Superficial antigens of Campylobacter (Vibrio) fetus: characterization of antiphagocytic component. - McCoy, E C (1975)
A glycoprotein responsible for the antiphagocytic properties of Campylobacter fetus has been identified by comparing cells of a wild-type strain with those of a mutant lacking this substance. The antiphagocytic component is demonstrable through electron microscopy as a discrete, negatively charged structure on the periphery of the cell. CLT is readily removed from the cell by mild extraction procedures and contributes to the inagglutinability in O antiserum normally displayed by C. fetus. Cells possessing this antigen are refractory to ingestion by macrophages except in the presence of specific antiserum. In its absence maximum phagocytosis occurs without a requirement for opsonins. It is concluded that the antiphagocytic component comprises a critical virulence factor of the bacterium.